Investigation of microbial adaptation to salinity variation for treatment of reverse osmosis concentrate by membrane bioreactor - Jang, Duksoo; Moon, Chungman; Ahn, Kyuhong; Shin, Hang-Sik; Hwang, Yuhoon (DESALINATION PUBL, 2015)
Even though reverse osmosis (RO) technologies are widely used for sustainable water reclamation, the control of concentrates containing a high concentration of dissolved matters originated from feed water should be considered. The effect of variations in salinity on biological wastewater treatment processes has to be evaluated for combined treatment with RO concentrate in sewage treatment plants. As a preliminary study, the effect of adaptation of seeding sludge on RO concentrate treatment was evaluated. The reactor inoculated by unadapted sludge had a significant inhibition on organic and ammonia removal. Especially, ammonia removal was completely inhibited and removal efficiency was maintained below 20% during 30d of operation. However, the removal efficiencies gradually increased with operation time, and it reached a similar performance to adapted sludge in 40d of operation. For a more quantitative study on a microbial adaptation strategy for variations on salt concentration (0-20g/L), lab-scale membrane bioreactors (7L working volume) with polypropylene hollow fiber membrane module (pore size 0.4m) were used with different adaptation strategies: instant and stepwise mode. The performance of the reactor deteriorated with an increasing salt concentration, but it recovered after adaptation periods (30-70 d). Moreover, the inhibition effect of salt could be minimized by a gradual increase in salt concentration. Analysis results for polymerase chain reaction-denaturing gradient gel electrophoresis indicated that nitrifiers were still present in high salinity. These results confirmed that an appropriate adaptation strategy should be determined for RO concentrate treatment.
Keywords: SEQUENCING BATCH REACTOR; WASTE-WATER; NUTRIENT REMOVAL; PERFORMANCE; SALT